Design and analysis of a high-gain dual-input single-output DC-DC converter for hybrid energy systems applications - Bharathi, Botta Venkata Vara Lova Kala; Satish, Raavi (Institute of Advanced Engineering and Science, 2023)
The high gain converters are one among the proven topologies that are found attractive for industrial and commercial applications. They deal with high power ratings like automobile headlamps, energy backup systems, and fuel cell electric vehicles (FCEV). In literature, most of the topologies were used a single duty ratio. This may not be reliable for high-duty cycle operation because to improve the voltage gain, the components will be increases. This paper proposes the time-sharing concept based on the non-isolated high step-up dc-dc converter. With the parallel-charged and series-discharged inductors, the proposed converter can produce high output voltage gains. The effectiveness of the proposed circuit configuration is verified in MATLAB/Simulink and the results are corroborated by theoretical analysis.